2014
DOI: 10.1016/j.jes.2014.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Application of fish index of biological integrity (FIBI) in the Sanmenxia Wetland with water quality implications

Abstract: Long-term changes of fish biotic integrity in the Sanmenxia Wetland, North China, since the 1950s were assessed using the fish index of biological integrity (FIBI). The water and sediment quality was evaluated by the water quality index (WQI) and sediment pollution index (SPI). The results showed that FIBI continuously decreased from 46 to 20 during the past 5 decades, which indicated that the fish community state shifted from fair to very poor conditions, and damming by itself did not affect the fish biotic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This study confirmed the prevalent use of mmIBI 08 for the right reason, as it was enough to designate the Korean streams and rivers on the biological health chart, i.e., from excellent to poor. The IBI model is primarily an adjustable model to the changing fish communities and various studies have explored it [2,5,13,19,41,50,67]. Water 2019, 11, x FOR PEER REVIEW 13 of 22 Figure 3.…”
Section: Regression Analyses On Biotic Integrity Modelsmentioning
confidence: 99%
“…This study confirmed the prevalent use of mmIBI 08 for the right reason, as it was enough to designate the Korean streams and rivers on the biological health chart, i.e., from excellent to poor. The IBI model is primarily an adjustable model to the changing fish communities and various studies have explored it [2,5,13,19,41,50,67]. Water 2019, 11, x FOR PEER REVIEW 13 of 22 Figure 3.…”
Section: Regression Analyses On Biotic Integrity Modelsmentioning
confidence: 99%